Terrible times : book 3 of the Eddie Dickens trilogy - Ardagh, Philip (Ardagh, Philip. Eddie Dickens trilogy, 2003)
Leaving his parents, his Mad Uncle Jack, and his Even Madder Aunt Maud at home at Awful End, Eddie Dickens, along with the color-blind Lady Constance, boards the ship the Pompous Pig on a mission to America.